INDUC WEB DEVELOPMENT TO IMPROVE THE PERFORMANCE OF UMKM IN TUBAN - Putri, Yogi Arditya Candani; Muhammad Bachtyar Rosyadi; Serlin Nurfita Sari; Ramadhani, M. David; Wasik Al Himam (Bahasa Indonesia, 2024)
This research focuses on the development of Web INDUC to support MSMEs in Tuban. Web INDUC is designed to increase the visibility of MSME products, facilitate transactions, and improve communication between MSMEs and customers. Although there are challenges such as development costs and infrastructure needs, this research uses a qualitative approach to solve these problems. The application development process involved the stages of requirement analysis, design, creation, and testing. System implementation was done using HTML, PHP, Bootstrap, MySQL. The results include features such as home page, product details, cart, and checkout. This research is expected to help the development of MSMEs in Tuban and improve their performance through an effective and efficient website.